Pulsed plasma nitriding of stainless steel - Torkar, Matjaž (Kovine zlitine tehnologije, 1995)
A use could be found for pulsed-plasma nitrided AISI 316L stainless steel in a wide range of biomedical applications, e.g. femoral and biarticular heads of joint prostheses. Forged samples of steel were pulsed-plasma nitrided at a temperature of 540°C for 24 hours to increase the hardness of the surface. During nitriding, the hardness of the ?$70 μ$? nitride layer uniformly increased to 958 HV 0.1. The hardness of steel below the nitride layer remained unchanged, 210 HV 0.1. The thickness of the layer depended on the process parameters. The research showed that nitriding of stainless steel for medical implants in pulsed plasma is feasible.
Keywords: jeklo; nerjavno jeklo; nitriranje; biomedicina